TRANSFORMATION OF COMMUNICATION THROUGH THE LENS OF LEADERSHIP IN AN ORGANIZATIONAL CONTEXT - Đukić, Tijana; Aćimović, Slaviša; Momčilović, Oliver; Marković, Svetlana; Nikolić, Miloš (ACADEMIC REVIEW, 2025)
This research aimed to investigate the influence of leadership styles on the evolution of communication within an organizational framework. The study used a survey research methodology to determine how employees felt about the firm’s communication procedures and leadership styles. The investigation demonstrated that leadership styles directly affect the levels of transparency, openness, trust, and employee involvement in decision-making. Democratic and transformational leadership styles are most conducive to fostering a constructive communication climate, whereas authoritarian methods may hinder communication and diminish motivation. The research finding underscores the necessity of cultivating leadership abilities that foster open dialogue, reciprocal communication, and active employee participation as essential requirements for effective management and organizational success.